2009
DOI: 10.3133/sir20095109
|View full text |Cite
|
Sign up to set email alerts
|

Mercury in fish, bed sediment, and water from streams across the United States, 1998-2005

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment, visit http://www.usgs.gov or call 1-888-ASK-USGS For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit http://store.usgs.gov Any use of trade, product, or firm names is for descriptive purposes only and does not imply endorsement by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(127 citation statements)
references
References 52 publications
(20 reference statements)
7
120
0
Order By: Relevance
“…In particular, we assumed the length of fishes as a reliable parameter for age estimates (Boening, 2000;Waldron and Kerstan, 2001;Scudder et al, 2009;Panfili et al, 2010;Basilone et al, 2011;Bacha et al, 2012) and, thus, reported HgT values vs. length to assess biomagnification of that contaminant with time. Statistically reliable and robust correlations were found between HgT mean values measured in muscles for size classes and length in S. pilchardus (r 2 = 0.75), E. encrasicolus (r 2 = 0.92), Trachurus trachurus (r 2 = 0.96), Diplodus annularis (r 2 = 0.98) and P. erythrinus (r 2 = 0.64) (Fig.…”
Section: Mercury Bioaccumulation Effects: Length/age Vs Hgt Contentmentioning
confidence: 99%
“…In particular, we assumed the length of fishes as a reliable parameter for age estimates (Boening, 2000;Waldron and Kerstan, 2001;Scudder et al, 2009;Panfili et al, 2010;Basilone et al, 2011;Bacha et al, 2012) and, thus, reported HgT values vs. length to assess biomagnification of that contaminant with time. Statistically reliable and robust correlations were found between HgT mean values measured in muscles for size classes and length in S. pilchardus (r 2 = 0.75), E. encrasicolus (r 2 = 0.92), Trachurus trachurus (r 2 = 0.96), Diplodus annularis (r 2 = 0.98) and P. erythrinus (r 2 = 0.64) (Fig.…”
Section: Mercury Bioaccumulation Effects: Length/age Vs Hgt Contentmentioning
confidence: 99%
“…Much of the current understanding of the controls on MeHg production, transport to primary aquatic habitats, and subsequent uptake and accumulation in aquatic foodwebs of lakes and streams in North America is based on research conducted in peatland, wetlands, and organic-rich surface-water environments of Canada and the northeastern USA. In contrast, comparatively little is known about the fundamental controls on Hg bioaccumulation in the Coastal Plain region of the southeastern USA, despite the recognized pattern of elevated fish Hg concentrations Glover et al, 2010;Guentzel, 2009;Krabbenhoft et al, 1999;Scudder et al, 2009) in this geographically extensive physiographic region (Fenneman, 1928(Fenneman, , 1938Vigil, 2000). Consequently, the remainder of this chapter will focus on the role of hydrology as a control on MeHg availability in Coastal Plain stream settings.…”
Section: Hydrology and Mehg Availability In Coastal Plain Streamsmentioning
confidence: 99%
“…A number of surface-water settings in North America are characterized by elevated levels of Hg bioaccumulation in fish Krabbenhoft et al, 1999;Scudder et al, 2009). Much of the current understanding of the factors contributing to elevated Hg bioaccumulation in aquatic habitats of North America is based on research conducted in the extensive peatland environments of Canada and in the organic-enriched surface waters of the northeastern USA, where Hg bioaccumulation in top predator fish and piscivorous bird species is well documented (Driscoll et al, 2007).…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…The case of fish Often, the answer to that question is not a happy one, and recommendations on how to deal with it are contradictory. In waterways, atmospheric deposition of mercury emitted from the combustion of fossil fuels, particularly coal-fired power plants, has led to widespread mercury contamination of fish in some areas (2,3) . At the same time, interest in the potential health benefits from consuming fish and fish oils is increasing.…”
Section: Linking Agricultural and Nutrition Policymentioning
confidence: 99%